2003
DOI: 10.1097/00002341-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Medial Rectus Muscle Injuries Associated With Functional Endoscopic Sinus Surgery

Abstract: Medial rectus muscle injury as a complication of FESS can vary markedly. Proper characterization and treatment are important, particularly with reference to the degree of direct MR injury (muscle tissue loss) and entrapment. Patients with severe MR disruption can benefit from intervention but continue to show persistent limitation of ocular motility and functional impairment. Prevention and early recognition and treatment of these injuries are emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 30 publications
0
68
0
2
Order By: Relevance
“…However, an attempt to recover the stump was indicated in 4 patients and the following results were not promising. Although marked improvement in primary ocular alignment was achieved after a MR posterior stump was reattached to the globe, there was rarely a recovery of the adduction function 12,15,23,25. Four patients in this study also obtained good ocular alignment through VRM transposition without any attempts to recover the MR stump.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, an attempt to recover the stump was indicated in 4 patients and the following results were not promising. Although marked improvement in primary ocular alignment was achieved after a MR posterior stump was reattached to the globe, there was rarely a recovery of the adduction function 12,15,23,25. Four patients in this study also obtained good ocular alignment through VRM transposition without any attempts to recover the MR stump.…”
Section: Discussionmentioning
confidence: 67%
“…It is seldom possible to examine the MR more posteriorly in the orbit through a conjuncival incision during conventional strabismus surgery 20. An orbital exploration may be indicated if the remaining posterior stump of MR is quite long and the patient presents within a few days after injury 12,15. However, the posterior stump may retract posteriorly, necessitating orbital surgery…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al [12] have analyzed 30 cases of medial rectus injury following FESS in the largest reported case series. They asserted that the MR injury following FESS can lead to one of the following four patterns:…”
Section: Discussionmentioning
confidence: 99%
“…Management involving a partially transected muscle is still under debate. Huang et al (8) reported that observation alone did not result in improvement, and that late repair led to little or no recovery. On the other hand, Hong et al (9) reported that the treatment with Botox® in the early period yielded improved outcomes over observation or surgery alone by preventing contraction of the antagonist muscle and more rapidly facilitating binocular single vision.…”
Section: Discussionmentioning
confidence: 99%